Progesterone sperm chemoattraction may be modulated by its corticosteroid-binding globulin carrier protein - Teves, Maria Eugenia (2010)
Progesterone, the main steroidal component secreted by the cumulus cells that surround the egg, chemotactically guides human spermatozoa. The aim of this work was to evaluate whether the carrier protein corticosteroid-binding globulin also participates in the sperm P chemotactic response. By means of videomicroscopy and image analysis, we observed that corticosteroid-binding globulin modulates the chemotactic activity of P, when a solution of corticosteroid-binding globulin + P is at the nanomolar range.